Module of Renewable Energy from the Earth's Gravity Based on Islam as Teaching Materials for Tadris IPA Study Program - Wiji Aziz Hari Mukti; Abdul Aziz bin Mustamine (Universitas Pakuan, 2022)
Gravity is a renewable energy source that has not been widely studied, although many scientists have researched and made prototypes of tools that use it. This article describes the development of a module of renewable energy from the Earth's gravity based on Islam as teaching material for the Tadris Science study program. This research used Research and Development (RD) method by Borg and Gall but modified only until the product revision stage. The validation results are 88.3% in the very good category from the material expert, 82.6% in the very good category from the media expert, and 89% in the very good category from the learning expert. This study concludes that students can use the developed product.